Towering spiritual and literary figure - Abd Razak, Dzulkifli (2007)
I am neither of the East nor of the West: no boundaries exist in my breast. "In this socalled borderless and globalised world, such words sounded more like a cliche, coming from any one of the G8 leaders or at least from the champions of globalisation. Only that this one is somewhat more poetic than rhetoric; more appealing to a palette of cultures, beliefs and religions, as compared to the usual empty lip service. The reason perhaps is the person who uttered them is one of the greatest spiritual and literary figures of all time.